2022
DOI: 10.3390/su141911876
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Salt-Affected Soils: Mechanistic Understanding of Interplay Factors and Reclamation Approaches

Abstract: Salt-affected soils contain high levels of soluble salts (saline soil) and exchangeable sodium (alkali soil). Globally, about 932 million ha (Mha), including 831 Mha of agricultural land, is salt-affected. Salinity and sodicity adversely affect soil microbial diversity and enzymatic activities, and thereby carbon and nitrogen dynamics and greenhouse gas (GHG) emissions from soils. In this review article, we synthesize published information to understand the impact of salinity and sodicity on GHG production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 139 publications
1
2
0
Order By: Relevance
“…FDA is subject to hydrolysis by various enzymes, including proteases, lipases, and esterases, resulting in the production of fluorescein, which exhibits correlations with parameters of microbial biomass such as the ATP content and oxygen consumption and can provide a measurement of the comprehensive soil microbial activity [47]. In the present study, a trend similar to that of DHA was observed for FDA (Figure 2) due to the fact that salinity alters the osmotic and matric potential of the soil solution, thereby making it difficult for microbes to obtain water and nutrients [48]. Considering all three soils and enzymes, the peak was consistent up to 28 DAI, which was similar to the findings reported by Perucci [49], who observed that soil enzyme activities were significantly higher within 30 days of the addition of municipal compost residues.…”
Section: Discussionsupporting
confidence: 51%
“…FDA is subject to hydrolysis by various enzymes, including proteases, lipases, and esterases, resulting in the production of fluorescein, which exhibits correlations with parameters of microbial biomass such as the ATP content and oxygen consumption and can provide a measurement of the comprehensive soil microbial activity [47]. In the present study, a trend similar to that of DHA was observed for FDA (Figure 2) due to the fact that salinity alters the osmotic and matric potential of the soil solution, thereby making it difficult for microbes to obtain water and nutrients [48]. Considering all three soils and enzymes, the peak was consistent up to 28 DAI, which was similar to the findings reported by Perucci [49], who observed that soil enzyme activities were significantly higher within 30 days of the addition of municipal compost residues.…”
Section: Discussionsupporting
confidence: 51%
“…In Poland, these emissions have increased by nearly 10%, and by 2030 their decrease is estimated at 5% compared to the level in 2020 (European Council 2020). In the EU, 80% of GHG emissions in agriculture are the CH 4 emissions from enteric fermentation and the N 2 O emissions from soils, while around 10% is responsible for manure management and related CH 4 emissions (EEA 2022, Fagodiya et al 2022). Ruminants are animals whose digestive tracts produce large amounts of methane .…”
Section: Introductionmentioning
confidence: 99%
“…Saline-alkali soils contain high levels of soluble salts. Globally, about 932 million hectares (M ha), including 831 million hectares of agricultural land, are affected by salt damage [1]. Saline-alkaline soils have little productivity [2].…”
Section: Introductionmentioning
confidence: 99%